The Correlation Between Social Capital with Fishermen's Household Income (Case Study in Tapak Paderi Beach Tourism Area, Bengkulu City) - Ranti Novpratiwi; Indra Cahyadinata; Nusril Nusril (AGRITROPICA : Journal of Agricultural Sciences, 2023)
This research was conducted in the tourist area of Tapak Paderi, Kebun Keling Village, Teluk Segara District, Bengkulu City. The sample of this study amounted to 39 people. Determination of the sample using Slovin theory and Proportional Stratified Random Sampling. This technique is used because the population is not homogeneous and proportionally stratified. The purpose of this study was to determine the level of: 1. Social capital of the Tapak Paderi fishing community. 2. The household income of Tapak Paderi fishermen. 3. The relationship between fishermen's social capital and fishermen's household income in Tapak Paderi. The research method used is 1. Descriptive statistical analysis 2. Fisher household income analysis 3. Spearman Rank analysis. The results of this study indicate that 1. The level of social capital owned by fishermen in the Tapak Padri area is included in the high category, with an average yield of 3.6. 2. The income level of fishermen's households in the Tapak Paderi area is IDR 3,082,998/month, or equivalent to IDR 1,541,499/person per month. It is included in the less prosperous category compared to the Bengkulu UMP in 2022. 3. The relationship between social capital and fishermen's household income is substantial.